Assessment of SARS-CoV-2 IgG and IgM antibody detection with a lateral flow immunoassay test. Issue 10 (October 2021) - Diani, Erica; Piccaluga, Pier Paolo; Lotti, Virginia; Di Clemente, Andrea; Ligozzi, Marco; De Nardo, Pasquale; Lambertenghi, Lorenza; Pizzolo, Francesca; Friso, Simonetta; Lo Cascio, Giuliana; Vianello, Alice; Marchi, Giacomo; et al.
Abstract: The dramatic impact of SARS-CoV-2 infection on the worldwide public health has elicited the rapid assessment of molecular and serological diagnostic methods. Notwithstanding the diagnosis of SARS-CoV-2 infection is based on molecular biology approaches including multiplex or singleplex real time RT-PCR, there is a real need for affordable and rapid serological methods to support diagnostics, and surveillance of infection spreading. In this study, we performed a diagnostic accuracy analysis of COVID-19 IgG/IgM rapid test cassette lateral flow immunoassay test (LFIA) assay. To do so, we analyzed different cohorts of blood samples obtained from 151 SARS-CoV-2 RT-PCR assay positive patients (group 1) and 51 SARS-CoV-2 RT-PCR assay negative patients (group 2) in terms of sensitivity, specificity, PPV, NPV and likelihood ratios. In addition, we challenged LFIA with plasma from 99 patients stored during 2015–2017 period. Our results showed that this LFIA detected SARS-CoV-2 IgM and/or IgG in 103 out of 151 (68.21%) samples of group 1, whereas no IgM and/or IgG detection was displayed both in the group 2 and in pre-pandemic samples. Interestingly, IgM and/or IgG positivity was detected in 86 out of 94 (91.49%) group 1 samples collected after 10 days from symptoms onset whereas only 17 out of 57 of group 1 samples obtained before day 10 were positive to SARS-CoV-2 specific antibodies. We also compared the performance of this LFIA test with respect to other four different LFIA assays in 40 serum samples from multiplex RT-PCR positive individuals. Within the limits of the study size, the results demonstrated that COVID-19 IgG/IgM rapid test cassette LFIA assay displayed valid performance in IgM and IgG detection when compared with the other four LFIA assays. Hence, this approach might be considered as an alternative point-of-care procedure for SARS-CoV-2 serological investigation. Abstract : SARS-CoV-2, COVID-19, LFIA assay, IgM and IgG.